Effects of mRNA-VEGF@USPIO magnetic resonance probe on endothelial injury in cerebral aneurysm - Zhao, Jiang; Li, Jingyi; Lu, Haitao; Chen, Yalan; Wang, Yanming; Liu, Xiangyang; Zhao, Hong (Frontiers in Neurology, 2025)
ObjectiveTo investigate the effects of a novel mRNA-VEGF@USPIO magnetic resonance probe on endothelial injury at cerebral aneurysms necks, and to evaluate its imaging performance and therapeutic potential, with a focus on exploring its potential as a therapeutic agent and preliminary imaging characteristics.MethodsThe mRNA-VEGF@USPIO probes were synthesized and thoroughly characterized. A rat model of cerebral aneurysm was successfully established. Vascular morphology, iron deposition, expression of endothelial cells-related factors, and vascular repair processes were evaluated using hematoxylin and eosin (HE) staining, Prussian blue staining, immunohistochemical staining, and magnetic resonance imaging (MRI).ResultsCompared to the model group, both mRNA-VEGF@USPIO probes and rosuvastatin significantly inhibited the proliferation of intimal and medial smooth muscle cells, reduced the risk of luminal thrombosis, and alleviated lumen stenosis. The mRNA-VEGF@USPIO probes additionally promoted the expression of endothelial cell growth-related factors CD31, CD34, VEGF, and vWF. No evidence of iron overload or iron-related toxicity was observed following probe administration. Furthermore, the probes provided high-quality imaging at various concentrations, clearly delineating the location and morphology of the aneurysm neck. Over the treatment course, MRI enabled serial visualization of the progressive recovery process.ConclusionThe mRNA-VEGF@USPIO probe demonstrated significant efficacy in promoting endothelial repair and regeneration at the neck of cerebral aneurysms. This theranostic agent not only offers a novel treatment strategy for cerebral aneurysms, but its favorable MRI imaging performance also lays a foundation for further evaluating its potential diagnostic value.